PWE-044 Inter-Tumour Heterogeneity in Hepatitis C Virus (HCV) Related Multi-Focal Hepatocellular Carcinoma (HCC). (17th August 2016) - Fateen, W; Wood, H; Berri, S; Wyatt, J; El- Meteini, M; Millson, C; Quirke, P
Abstract : Introduction: Curative therapies improve overall survival by more than 60 months on a small proportion of patients with HCC however the majority of patients are diagnosed with non curable, mostly multi-focal HCC. There are two theories for the development of multifocal HCC. First is intrahepatic metastasis where the new cancer would inherit genetic properties from the index cancer. Second is de novo development of HCC where both cancers are expected to have genetically diverse properties. We aimed to evaluate the presence and frequency of intrahepatic metastasis versus de novo carcinogenesis in HCV related multi-focal HCC. Methods: We studied DNA copy number profiles of 70 HCV-related hepatocellular cancers found in 19 surgically removed liver specimens from 18 patients. Differences in copy number patterns were objectively analysed using Pearson's correlations between normalised, non-smoothed, non-segmented ratios (n = 27, 180 per each sample). Fisher r to z to r transformation was used in calculation of the average coefficients. Results: Livers containing 2 or 3 nodules (n = 10 livers) had an average cancer correlation coefficient of 0.395 and only 20% of them (n = 2/10) harboured cancers with coefficients >0.5. Livers containing 4 or more nodules (n = 9 livers) had an average cancer correlation coefficient of 0.620 and 89% of them (n = 8/9) harboured cancers with coefficients >0.5. The higher correlation coefficient may indicate that livers with a larger number of nodules are more likely to harbour genetically similar cancers then liver with a smaller number of nodules. This implies that intrahepatic metastasis starts to occur at a more advanced stage of liver disease and that de novo carcinogenesis takes place at an earlier stage. Conclusion: This study confirms that both processes exist. The occurrence of de novo carcinogenesis leads to emergence of genetically diverse cancers within the same liver. Our data suggests that this occurs at an earlier stage of multifocal spread. Intrahepatic metastasis leads to occurrence of genetically similar cancers within the same liver. This possibly occurs when HCC's are more established. More cases are needed to validate the sequence of events in hepatocarcinogenesis. This is knowledge is clinically relevant as cancers with diverse genetic profiles are practically more difficult to manage. Disclosure of Interest: W. Fateen: None Declared, H. Wood: None Declared, S. Berri Employee of: Illumina, J. Wyatt: None Declared, M. El- Meteini: None Declared, C. Millson: None Declared, P. Quirke: None Declared